1995
DOI: 10.1002/aja.1002040410
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the expression of fibroblast growth factor receptors mark distinct stages of chondrogenesis in vitro and during chick limb skeletal patterning

Abstract: Members of the fibroblast growth factor (FGF) family of growth factors are key regulators of limb skeletal patterning and growth. Abnormal expression of FGFs or mutations in their receptors (fgfrs) result in skeletal disorders. Here we show that changes in the expression of f&s are intrinsic properties of differentiating cartilage. In mesenchymal micromass cultures differentiating into cartilage, as in ovo, fgfr 1 mRNA was found predominantly in undifferentiated, proliferating mesenchyme, f& 2 in precartilage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 80 publications
3
45
0
Order By: Relevance
“…3A). These patterns of expression have been observed in chicken, mouse, and hu- man limb development (Orr-Urtreger et al 1991;Peters et al 1992;Szebenyi et al 1995;Delezoide et al 1998). Later in skeletal development, Fgfr1 and Fgfr2 expression persists in the perichondrium and periosteum in patterns that suggest expression in the osteoblast lineage .…”
Section: Fgf Receptor Expressionmentioning
confidence: 84%
“…3A). These patterns of expression have been observed in chicken, mouse, and hu- man limb development (Orr-Urtreger et al 1991;Peters et al 1992;Szebenyi et al 1995;Delezoide et al 1998). Later in skeletal development, Fgfr1 and Fgfr2 expression persists in the perichondrium and periosteum in patterns that suggest expression in the osteoblast lineage .…”
Section: Fgf Receptor Expressionmentioning
confidence: 84%
“…We compared the expression pattern of FGF-2 and Pax-3 and found that migrating myogenic cells were capable of expressing FGF-2. Moreover, these cells also expressed FREK, the FGF receptor (Marcelle et al, 1995;Szebenyi et al, 1995). Because our Blindwell chemotactic assays showed that FGF-2 can stimulate chemokinesis as well as chemotaxis, it is possible that myogenic cells maintain their own ability to migrate in the limb by producing FGF-2, which then acts through some form of autocrine mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…1A) Fgfr2 expression is increased (compared with the surrounding mesenchyme) and initially overlaps with domains of Sox9 expression (Orr-Urtreger et al 1991;Peters et al 1992;Szebenyi et al 1995;Delezoide et al 1998;Eswarakumar et al 2002;Sheeba et al 2010). Fgfr1 is more uniformly expressed throughout limb bud mesenchyme.…”
Section: Fgf Signaling During Skeletal Developmentmentioning
confidence: 99%
“…Fgfr1 is more uniformly expressed throughout limb bud mesenchyme. Although Fgfr3 and Fgfr4 are excluded from distal limb bud mesenchyme, these Fgfrs are expressed in more proximal locations in tissues corresponding to developing muscle (OrrUrtreger et al 1991;Peters et al 1992;Szebenyi et al 1995;Delezoide et al 1998;Sheeba et al 2010). Cells in the periphery of the condensation that will form perichondrium and periosteum express both Fgfr1 and Fgfr2 ( Fig.…”
Section: Fgf Signaling During Skeletal Developmentmentioning
confidence: 99%